2006
DOI: 10.1017/s0022112006000528
|View full text |Cite
|
Sign up to set email alerts
|

Forced laminar-to-turbulent transition of pipe flows

Abstract: This paper presents the results of investigations into particular features of laminarto-turbulent transition of pipe flows. The first part considers transitional flows that occur 'naturally', i.e. without any forcing, when a critical Reynolds number is reached. Measurements are reported that were carried out to study the intermittent nature of pipe flows before they become fully turbulent. The second part of the paper concentrates on forced laminar-to-turbulent transition where the forcing was achieved by ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 10 publications
5
55
0
Order By: Relevance
“…They concluded that a critical amplitude of disturbance was needed to cause a transition and it depends on the Reynolds number. Durst &Ünsal (2006) highlighted the influence of the disturbed wall fence height and the results showed a dependence of critical Reynolds number on the normalized height of their disturbances.…”
Section: Introductionmentioning
confidence: 94%
“…They concluded that a critical amplitude of disturbance was needed to cause a transition and it depends on the Reynolds number. Durst &Ünsal (2006) highlighted the influence of the disturbed wall fence height and the results showed a dependence of critical Reynolds number on the normalized height of their disturbances.…”
Section: Introductionmentioning
confidence: 94%
“…The size of the ring-type constriction is based on an a previous study by Durst and Ü nsal 29 who provide an indication of the mean Reynolds number at which transition is expected to occur. We should note here that the type of disturbance may have an influence on the critical Reynolds number.…”
Section: Experimental Techniques a Flow Facilitymentioning
confidence: 99%
“…For the axial component, a large overshoot is shown for Re m ¼ 2388, a phenomenon reported before. 29 …”
Section: B Transition Of Steady Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…It is seen that the velocity pro¦les at L/d = 65 and 200 (L = 1300 and 4000 mm) are fully turbulent, whereas the velocity pro¦le at L/d = 43.5 (L = 870 mm) exhibits a characteristic §at part in the §ow core indicative of the fact that the channel §ow in the latter case was not fully turbulent yet. [20] is given in Fig. 9b.…”
Section: Turbulent Jetmentioning
confidence: 99%